PENGARUH JENIS KELAMIN TERHADAP PRODUKSI KARKAS SAPI POTONG DI SULAWESI TENGA - Dien, Rusdin (FAPETKAN UNTAD, 2011)
The objective of this research is to study and determine the extent of the influence of breed and sex on carcass percentage and edible non-carcass of beef in Central Sulawesi. This experiment was an analytical descriptive with survey method. Primary data collected in this experiment were taken from the respondents as a key person. Data collection technique was a direct recording method on the activities occurred at the abattoir. Data recorded were breed, sex, live weight and weight of animal product after slaughtering (weight and carcass percentage). Recording of number and breed of cattle was done for a week at the abattoir in Sigi, Parigi Moutong, Poso, Banggai and Toli – Toli regencies. Data recorded from 100 cattle was statistically analyzed with T – Test. The results of study indicated that carcass percentage of bull (47.68%) was significantly lower than the carcass percentage of those heifers (49.437%). Key words : Beef cattle, sex and carcass percentage.